Comparison of Cesarean Delivery Rates in Urban and Rural Hospitals [1]. (May 2015) - Chang, Ann Lee; Yoshino, Kurt D.; Sentell, Tetine; Miyamura, Jill; Maddock, Jay; Pacheco, Misty
Abstract : INTRODUCTION: Some studies have demonstrated hospital and geographic variation in cesarean delivery rates. Our objective is to compare primary cesarean delivery rates in urban and rural hospitals. METHODS: We examined all hospital admissions of women who delivered a singleton live-born neonate in the state of Hawaii from January 2010 to December 2011 using the Hawaii Health Information Corporation database. Women with a history of prior cesarean delivery were excluded. Hospitals were divided into two categories: rural and urban. Primary cesarean delivery rates as well as common reasons for primary cesarean deliveries were examined. RESULTS: Of the 30, 647 women who met criteria for our study, 7, 717 (25.3%) delivered in rural hospitals. Women who delivered at rural hospitals had fewer risk factors for cesarean delivery, including advanced maternal age, preterm delivery, pregestational diabetes, and hypertensive disease. However, rural hospitals had a higher primary cesarean delivery rate of 21.1% compared with 15.3% in the urban hospitals ( P< .001). Even after adjusting for maternal risk factors and common indications for cesarean delivery, women who delivered at rural hospitals had a more than twofold risk for cesarean delivery (adjusted odds ratio 2.46, 95% confidence interval 2.26–2.70). CONCLUSION AND IMPLICATION: In a geographically isolated population, rates of cesarean delivery are significantly higher in rural hospitals. Because reasons for this finding are unclear, this disparity should be investigated further.